Pyramid - Macaulay, David (Boston : Houghton Mifflin, 1975)
Text and black-and-white illustrations follow the intricate step-by-step process of the building of an ancient Egyptian pyramid.
Keywords: Pyramids -- Egypt -- Design and construction -- Juvenile literature; Pyramids; Egypt -- Civilization